2010
DOI: 10.1016/j.neurobiolaging.2008.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Vascular health risks and fMRI activation during a memory task in older adults

Abstract: Vascular problems increase Alzheimer's disease (AD) risk, but the nature of this relationship remains unclear. Older adults having genetic risk for AD show regionally increased functional magnetic resonance imaging (fMRI) activity during memory, possibly representing compensation for a genetically induced neural deficit. We investigated whether vascular health risks, which similarly could lead to neuropsychological deficits, also showed increased fMRI activity during a memory task performed by 30 cognitively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Furthermore, the increased or decreased activation between a resting state positron emission tomography scan and a task-related fMRI scan require different interpretations. Another recent study by Braskie et al (2010) using fMRI found that during a memory task, participants with higher systolic blood pressure and body mass index had increased activation in the posterior cingulate cortex and parietal cortex. Our results are somewhat consistent with this finding since both found that increased CV risk was associated with higher activation in task-related brain regions.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the increased or decreased activation between a resting state positron emission tomography scan and a task-related fMRI scan require different interpretations. Another recent study by Braskie et al (2010) using fMRI found that during a memory task, participants with higher systolic blood pressure and body mass index had increased activation in the posterior cingulate cortex and parietal cortex. Our results are somewhat consistent with this finding since both found that increased CV risk was associated with higher activation in task-related brain regions.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, memory function is well described as a distributed process (Mesulam, 1990), and the brain substrates and modifiers of this process are highly variable, particularly in a cognitive aging context (Braskie, et al, 2010, Head, et al, 2008, Raz and Rodrigue, 2006, Verhaeghen, et al, 1993). Vascular risk factors, diabetes, and level of physical activity, sleep duration, and sleep quality have all been linked to brain structure and function necessary for supporting memory processes (den Heijer, et al, 2003, Goel, et al, 2009, Guzman, et al, 2013, Harrison and Horne, 2000, Honea, et al, 2009, Mander, et al, 2013, Raz and Rodrigue, 2006, Voss, et al, 2010, Zlokovic, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CVD has also been associated with structural and functional alterations in the fronto-parietal and medial temporal lobe regions, including reduced brain volume [4042], decreased white matter integrity [43, 44], reductions in cerebral blood flow [45, 46] and altered fMRI activity in the hippocampus, cingulate gyrus and fronto-parietal regions during memory [47, 48] and executive function tasks [4952]. Structural and functional brain alterations associated with aging and CVD induce predictable cognitive impairments such as deficits in episodic memory and executive dysfunction [5355].…”
Section: Introductionmentioning
confidence: 99%